(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The article presents scientific conclusions and statistical analyzes about the position of women in society and increasing their socio-political and economic activity, as well as the role of foreign experiences in this process, as well as the results of studying foreign experiences. The specific participation, activity, and opportunities of women in the current modern science and new innovative technological sphere have been analyzed based on available sources.